Public perception of environmental problems in Central Asia: results from the Life in Transition survey - Imomjon Khamidov; Bekhzod Egamberdiev (ZBW - Leibniz Information Centre for Economics, 2025)
Environmental issues adversely impact air quality, biodiversity, and socio-economic conditions in Central Asia. This paper utilizes the Life in Transition dataset to analyse climate change awareness and willingness to mitigate among populations from Kazakhstan, the Kyrgyz Republic, Tajikistan, and Uzbekistan. Our findings reveal that public perceptions of environmental problems vary, with the highest concerns about air pollution, waste, species loss, temperature fluctuations, natural disasters, and disease spread noted in Uzbekistan and the Kyrgyz Republic. Conversely, awareness and concern for environmental issues in Tajikistan are relatively low.
Keywords: Q54; Q56; P48; 330; environmental problems; climate change; public perception; willingness to contribute; Central Asia